First steps towards internationalization in the Universidad Michoacana de San Nicolás de Hidalgo - Vega Cano, Rosa (IE Revista de Investigación Educativa de la REDIECH, 2021)
Internationalization has become one of the main trends in higher education and an imperative for these institutions to be able to respond to changes and adapt to their environment, which is why this work aimed to study how the international dimension is being addressed at the Universidad Michoacana de San Nicolás de Hidalgo. To do this, a qualitative methodological approach was followed; institutional documents and databases were reviewed, and semi-structured interviews were conducted with the staff of the Department of Linking and Development, an administrative area in which information on the subject is concentrated. The general conclusion resulted is that this University has not integrated the international dimension into its substantive functions, at most it has implemented some internationalization programs in a marginal way, isolated and without a clear objective, and that to lay the foundations and promote the internationalization process it is necessary to carry out an academic, organizational, administrative and political reconfiguration, which constitutes, at the same time, the main challenge that this institution has to face.